ENHANCING STUDENTS’ TRANSLATION ABILITY THROUGH GROUP WORK - Rulik Setiani (Edukasi Lingua Sastra, 2020)
Translation is a compulsory subject which must be mastered by the sixth semester students of STKIP Muhammadiyah Kotabumi, by mastering this course, they automatically also must master the mastery of English vocabulary and grammar. One of the ways done by lecturer in improving the ability to translate Indonesian into English and vice versa by the application of group work technique, in this case before learning begins the lecturer needs to prepare a syllabus, semester learning plan, teaching materials, and also the media used by lecturer in the learning process of translation courses. The first step taken by the lecturer in this case is Plan, while in the main activity through group work technique, the lecturer asks students to make groups of 3 to 4 students to translate the text given by the lecturer, when they are finished, the lecturer checks the results of the group by submitting the answers or also discussed together, other ways of group work is in pairs. The lecturer also gives appreciation to each group that can answer correctly; at this stage the lecturer also observes the learning process of students. The last stage is reflection, at this stage the lecturer presents the findings during the learning process, this aims to improve the learning process in the next stage is better and increased.